CP-090 Solid oral dosage forms in paediatric patients – a cost-savings investigation. (24th February 2014) - Lajoinie, A; Kassaï, B; Terry, D
Abstract : Background: Oral liquid drugs, commonly used in children, present numerous disadvantages. Solid oral forms have greater stability, provide higher drug compliance in children and markedly reduce costs. Two limits could explain the difficulties of solid drug use in children: swallowing difficulties and low flexibility of the solid dosage. Purpose: To assess the suitability for substitution of prescribed oral liquid medicines with solid forms for children over 2 years. The cost savings that could be made if liquid medicines were substituted with an acceptable solid form were determined using NHS prices. Materials and methods: Substitution suitability for dispensed liquid medicines during one week (7–13th January 2013) in Birmingham Children's Hospital was determined (i) screening for existence of a marketed solid oral alternative then (ii) evaluating acceptability of solid forms in terms of posology and pill size depending on children's age (EMA guidelines). Treatment costs were calculated on the basis of providing treatment for 28 days or prescribed duration for short term treatment. Results: Of the 476 liquid medicines dispensed, 90% were available as a marketed solid form. Considering solid form dosage acceptability, 80% of liquid medicines could be substituted with a solid form. Only 41% of liquid formulations could be substituted when additionally considering pill size. Drug cost savings that could follow the substitution of liquid medicine with an acceptable solid form for dosage and size would be £4, 951 and £8, 550 in one week respectively for hospital and community, corresponding to an estimate projected annual saving of £238K and £410K (one hospital). Conclusions: Surprisingly, almost all liquid medicines were available in an acceptable tablet dosage. Whilst not all children over 2 years will be able to swallow tablets, this study has shown the importance of potential drug cost savings if solid forms were used in children and may provide a theoretical basis for teaching how to swallow tablets. No conflict of interest.